Brazilian guidelines for the pharmacological treatment of the pulmonary symptoms of cystic fibrosis. Official document of the sociedade brasileira de pneumologia e tisiologia (sbpt, brazilian thoracic association) - Athanazio, Rodrigo Abensur; Tanni, Suzana Erico [UNESP]; Ferreira, Juliana; De Tarso Roth Dalcin, Paulo; De Fuccio, Marcelo B.; Esposito, Concetta; Canan, Mariane Gonçalves Martynychen; Coelho, Liana Sousa [UNESP]; De Cássia Firmida, Mônica; De Almeida, Marina Buarque; Marostica, Paulo José Cauduro; De Freitas Velloso Monte, Luciana; et al. (Sociedade Brasileira de Pneumologia e Tisiologia, 2023)
Cystic fibrosis (CF) is a genetic disease that results in dysfunction of the CF transmembrane conductance regulator (CFTR) protein, which is a chloride and bicarbonate channel expressed in the apical portion of epithelial cells of various organs. Dysfunction of that protein results in diverse clinical manifestations, primarily involving the respiratory and gastrointestinal systems, impairing quality of life and reducing life expectancy. Although CF is still an incurable pathology, the therapeutic and prognostic perspectives are now totally different and much more favorable. The purpose of these guidelines is to define evidence-based recommendations regarding the use of pharmacological agents in the treatment of the pulmonary symptoms of CF in Brazil. Questions in the Patients of interest, Intervention to be studied, Comparison of interventions, and Outcome of interest (PICO) format were employed to address aspects related to the use of modulators of this protein (ivacaftor, lumacaftor+ivacaftor, and tezacaftor+ivacaftor), use of dornase alfa, eradication therapy and chronic suppression of Pseudomonas aeruginosa, and eradication of methicillin-resistant Staphylococcus aureus and Burkholderia cepacia complex. To formulate the PICO questions, a group of Brazilian specialists was assembled and a systematic review was carried out on the themes, with meta-analysis when applicable. The results obtained were analyzed in terms of the strength of the evidence compiled, the recommendations being devised by employing the GRADE approach. We believe that these guidelines represent a major advance to be incorporated into the approach to patients with CF, mainly aiming to favor the management of the disease, and could become an auxiliary tool in the definition of public policies related to CF.
Diretrizes brasileiras para o tratamento farmacológico pulmonar na fibrose cística. Documento oficial da Sociedade Brasileira de Pneumologia e Tisiologia
Keywords: Clinical practice guide; Cystic fibrosis; Cystic fibrosis/drug treatment; GRADE approach